The path to sustainability in the pharmaceutical industry: green HRM’s influence on employee behavior through psychological green climate - Bassant Adel Mostafa (Future Business Journal, 2025)
Abstract The emerging need to attain organizational sustainability calls for a new green perspective centered on effectively deploying green practices. Despite growing interest in green human resource management, studies on green practices remain inadequate and still arise in the context of developing countries. This study investigates the implementation of green human resource management practices in the pharmaceutical industry in Egypt and their impact on green organizational citizenship behavior while considering the mediating role of a psychological green climate. Using an exploratory mixed-methods approach, four primary green human resource management practices were extracted from a literature review and field data through semi-structured interviews. A survey was then used to gather data from a judgmental sample of 245 employees selected from the pharmaceutical industry in Egypt. Partial least squares structural equation modeling was used for the data analysis. The results revealed that pharmaceutical organizations moderately implement green practices, with ‘green recruiting’ and ‘green training’ having the highest impact. In contrast,’green performance management and compensation’ had the least impact. The path coefficient test showed a direct and indirect effect of green human resource management practices on green organizational citizenship behavior through a psychological green climate. The research’s implications add to the body of knowledge by establishing a research framework that contributes to human resource management and environmental studies literature that capitalizes on the ability–motivation–opportunity framework in providing policymakers in pharmaceutical organizations with insights on how to link their green human resource management practices and psychological green climate for maximized green organizational citizenship behavior strategically.